ANSWER
f(f(f(x - 1))) = x + 5
Step-by-step explanation
We have the function:
f(x) = x + 2
First, let us find f(x - 1). To do that, replace x with x - 1:
f(x - 1) = x - 1 + 2
f(x - 1) = x + 1
To find f(f(x - 1)), we need to replace the value of x in the function with the value of f(x - 1).
That is:
f(f(x - 1)) = f(x + 1) = x + 1 + 2
f(f(x - 1)) = x + 3
To find the value of f(f(f(x - 1))), we replace the value of x in the function with the value of f(f(x - 1)):
f(f(f(x - 1))) = f(x + 3) = x + 3 + 2
f(f(f(x - 1))) = x + 5
That is the answer.